Pengaruh Person Organization Fit, Organizational Commitment, dan Job Satisfication Terhadap Intention to Stay pada Karyawan Generasi Z yang Bekerja di Kabupaten Karanganyar - Nabila Iswara; Nike Larasati (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Research on Generation Z expectations and their consequences in the workplace in various countries remains relatively scarce. This scarcity motivated this study to analyze the antecedents of intention to stay among Gen Z in Indonesia, specifically in Karanganyar Regency. In line with this phenomenon and the research gap, this study will replicate previous research to test the consistency of research on the influence of person-organization fit, organizational commitment, and job satisfaction on intention to stay among Generation Z in Karanganyar Regency. The population of this study was Generation Z employees working in private and government companies in Karanganyar Regency, an unknown number of whom were selected. The sample size was 100 employees, calculated using the Leedy formula. The sample was drawn using a purposive sampling technique with the following criteria: (1) Born between 1997 and 2004; (2) Working in the Karanganyar area; (3) Having a minimum of 1 year of service; and (4) Generation Z employees being at least 21 years old. Data collection used a questionnaire scored on a 5-point Likert scale. Data analysis used multiple linear regression analysis, and hypothesis testing used the t-test. The t-test results show that (1) Person-organization fit has a positive and significant effect on the intention to stay among Generation Z in Karanganyar Regency, supported by a p-value of 0.001 < 0.05, thus confirming Hypothesis 1. (2) Organizational commitment has a positive and significant effect on the intention to stay among Generation Z in Karanganyar Regency, supported by a p-value of 0.000 < 0.05, thus confirming Hypothesis 2. (3) Job satisfaction has a positive and significant effect on the intention to stay among Generation Z in Karanganyar Regency, supported by a p-value of 0.000 < 0.05, thus confirming Hypothesis 3.